Simulated regional dust cycle in the Carpathian Basin and the Adriatic Sea region during the Last Glacial Maximum - Ludwig, Patrick; Gavrilov, Milivoj B.; Markovic, Slobodan B.; Ujvari, Gabor; Lehmkuhl, Frank (Quaternary International, 2020)
The climate and environmental conditions in the Carpathian Basin and the adjacent northern Italy/Adriatic region during the Last Glacial Maximum (LGM) exhibit some major differences, as compared to present-day conditions. For instance, high accumulation rates recorded in loess deposits point to an active dust cycle during the LGM. Here, we investigate the climate conditions and provide new insights into the regional dust cycle based on regional climate simulations for both LGM and present-day boundary conditions. The high-resolution model output (grid spacing of ∼8.5 km) is in good agreement with available proxy data, showing much colder (particularly during winter) and drier conditions during the LGM over the model domain. Further, the simulated aeolian dust cycle of small grain size particles (<20 μm) is investigated in more detail for LGM conditions. Highest dust emissions are simulated to the east of the Alpine ice sheet and in the Kvarner Bay region. In the northern Carpathian Basin, dust deposition plumes indicate prevailing northerly (NW, N and NE) winds. Strong Bora winds flowing down the slopes of the Dinaric Alps appear to play a major role in the local to regional dust cycle in the northern Adriatic region. From a seasonal perspective, the dust cycle is most active during winter and spring. A closer look at climate and environmental conditions at key areas reveals that high mean wind speeds and low precipitation rates correlate well with the high dust emissions during winter and spring. In contrast, lower wind speeds, increasing precipitation and the greening of vegetation prevent high dust emissions during summer and autumn. An additional analysis of the occurrence frequency of cyclonic circulation patterns in the Adriatic shelf region reveals that individual passing cyclones played an important role in the transport of dust particles from the alluvial Po plain towards the eastern Adriatic loess stacks.